Don't Step Into Your Parent's Shoes – How Exploitation and Exploration Affect Spin-out Growth - Simon Heinrichs; Sascha Walter (ZBW - Leibniz-Informationszentrum Wirtschaft, 2013)
This study examines how different organizational learning strategies (i.e., exploration or exploitation) impact the sales growth of technology spin-outs, and the role of the parent firm in this context. Using knowledge-based and learning views of the firm, we propose that spin-out performance benefits from exploration, but suffers from exploitation. Results based on a sample of 134 spin-outs support these arguments. Additionally, parent goodwill reinforced the positive effect of exploration, whereas high market similarity to the parent firm increased the negative effect of exploitation.
Keywords: M13; 650; Spin-outs